2010
DOI: 10.1016/j.schres.2010.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Regional prefrontal cortex gray matter volumes in youth at familial risk for schizophrenia from the Harvard Adolescent High Risk Study

Abstract: Background Regional prefrontal cortex gray matter reductions have been identified in schizophrenia, likely reflecting a combination of genetic vulnerability and disease effects. Few morphometric studies to date have examined regional prefrontal abnormalities in non-psychotic biological relatives who have not passed through the age range of peak risk for onset of psychosis. We conducted a region-of-interest morphometric study of prefrontal subregions in adolescent and young adult relatives of schizophrenia pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…15 A pooled sample of 4 European twin cohorts rejected a significant phenotypic correlation between total grey matter volume and schizophrenia. 18 Notwithstanding these findings, subtle grey matter volume reductions have been frequently described in individuals unaffected by schizophrenia but at familial risk for the disorder; [31][32][33] this finding has also been supported by a meta-analysis. 20 More recently, unaffected sibling data sets have confirmed significant deficits in the patients' grey matter volume, but have either failed to detect significant deficits in their unaffected siblings, or detected only marginal effects.…”
Section: J Psychiatry Neurosci 2017;42(2)mentioning
confidence: 85%
“…15 A pooled sample of 4 European twin cohorts rejected a significant phenotypic correlation between total grey matter volume and schizophrenia. 18 Notwithstanding these findings, subtle grey matter volume reductions have been frequently described in individuals unaffected by schizophrenia but at familial risk for the disorder; [31][32][33] this finding has also been supported by a meta-analysis. 20 More recently, unaffected sibling data sets have confirmed significant deficits in the patients' grey matter volume, but have either failed to detect significant deficits in their unaffected siblings, or detected only marginal effects.…”
Section: J Psychiatry Neurosci 2017;42(2)mentioning
confidence: 85%
“…Neuroimaging studies have revealed that, relative to controls, offspring of patients with schizophrenia (SzO) exhibit volumetric reductions in total brain volumes 10,11 , the amygdala-hippocampal complex 10,[12][13][14] and basal ganglia, 11,14 as well as grey matter volume decrease in frontal 13,15 , temporal, 16 and parietal cortices 13 . Grey matter volume reductions in these cortical regions have also been related to prodromal symptomatology 13,15 . Conversely, studies in child and adolescent offspring of patients with BD (BdO), have yielded largely negative findings 17,18 , with a single exception concerning increased grey matter volume in the left hippocampal-parahippocampal gyrus 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The neuroimaging data so far has been limited by small sample sizes, especially in BdO [17][18][19] , ages centred M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 in late, rather than early adolescence in SzO 13,15 , and an approach driven by predefined regions of interest (ROI) in the majority of the above studies. In addition, a number of samples have also included other first-and second-degree relatives [13][14][15] , limiting extrapolation of findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Magical Ideation Scale (MIS) (Eckblad & Chapman, 1983) enquires about ideas of reference and odd beliefs (e.g., "Good luck charms don't work", keyed "false"). In previous work using the FHR-SCZ sample compared to healthy controls Rosso et al, 2010), we demonstrated that FHR-SZ were significantly impaired on revised physical anhedonia but not on PAS or MIS. The results of the FHR-AFF group were not reported in those papers.…”
Section: Measures Of Psychosis Pronenessmentioning
confidence: 54%